2003
DOI: 10.1161/01.hyp.0000060689.38912.cb
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Renal Angiotensin-Converting Enzyme 2 in Diabetic Nephropathy

Abstract: Abstract-ACE2, initially cloned from a human heart, is a recently described homologue of angiotensin-converting enzyme (ACE) but contains only a single enzymatic site that catalyzes the cleavage of angiotensin I to angiotensin 1-9 [Ang(1-9)] and is not inhibited by classic ACE inhibitors. It also converts angiotensin II to Ang(1-7). Although the role of ACE2 in the regulation of the renin-angiotensin system is not known, the renin-angiotensin system has been implicated in the pathogenesis of diabetic complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
330
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(365 citation statements)
references
References 30 publications
28
330
7
Order By: Relevance
“…Given that ACE2 expression is altered not only in the rat diabetic kidney [4] but also in human kidney disease [5], an association between gene variants and diabetic nephropathy could be expected. However, the present study did not detect any such association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ACE2 expression is altered not only in the rat diabetic kidney [4] but also in human kidney disease [5], an association between gene variants and diabetic nephropathy could be expected. However, the present study did not detect any such association.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is highly expressed in kidney, testis and heart and has been implicated in hypertension and cardiovascular disease [3]. Interestingly, ACE2 production is decreased in rat diabetic kidney [4] and is altered in human kidney disease such that neo-expression of ACE2 occurs in glomerular and peritubular capillary endothelium [5]. The only study published to date on ACE2 polymorphisms and essential hypertension reported no association [6].…”
Section: Introductionmentioning
confidence: 99%
“…128 In the kidney, ACE2 has a distribution similar to ACE, with major localization in renal tubules. [128][129][130] It has been suggested that both mRNA and protein expression of ACE2 are reduced in kidney biopsy specimens from type 2 diabetic patients with nephropathy compared with normal controls or patients with other renal disease. 131 In another study, ACE2 levels in kidney biopsy of diabetic patients were reduced only at the protein level, not at the mRNA level, and only in the tubulointerstitial region, not in the glomeruli, compared with non-diabetic controls.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…131 In another study, ACE2 levels in kidney biopsy of diabetic patients were reduced only at the protein level, not at the mRNA level, and only in the tubulointerstitial region, not in the glomeruli, compared with non-diabetic controls. 132 In experimental models of diabetes-associated kidney disease, it has been shown that ACE2 may be reduced 129 or elevated. 133 Reasons for this discrepancy may be attributed to the duration of diabetes and different methodology in assessing ACE2, gene or protein expression, or their activity.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…The samples from the control kidneys were used as the calibrator and given an arbitrary value of 1, and the treatment groups were compared with this calibrator [26].…”
Section: Real-time Rt-pcrmentioning
confidence: 99%